Native Teacher’s Perception on Students’ Language Learning Competence - Maulida, Maulida; Salmiah, Maryati (International Journal of English and Applied Linguistics (IJEAL), 2025)
This qualitative case study explores native English teachers' perceptions of language learning competence among fifth-semester students in the English Education Department. Through semi-structured interviews with one native speaker from the United States participating in the guest lecture program, this research examines students' competencies across four language skills: listening, speaking, reading, and writing. The findings reveal that students demonstrate excellent listening abilities but struggle with colloquial American expressions and culturally-specific phrases in structured classroom contexts. Their speaking skills are characterized as fluent with strong explanatory abilities, though confidence levels vary significantly due to Indonesian cultural values emphasizing humility and hierarchy. Reading competence is assessed as strong, particularly with narrative texts, while academic articles present greater challenges. Writing assessment was limited due to the curriculum structure, though students showed excellence in academic writing tasks. The study identifies six underlying factors shaping native speaker perceptions: dominance of formal academic language learning, influence of Indonesian cultural values on self-expression, limitations of unbalanced learning methodology, adaptive capacity in multi-skill communication, differences in cross-cultural expectations, and limited authentic learning contexts. These findings highlight the need for curriculum reform incorporating diverse authentic materials, balanced skill development, and cultural adaptation strategies to bridge the gap between formal academic learning and real-world communication needs in Indonesian English language education.